1984
DOI: 10.2105/ajph.74.12.1340
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of injuries among 87,000 Massachusetts children and adolescents: results of the 1980-81 Statewide Childhood Injury Prevention Program Surveillance System.

Abstract: This study describes the incidence of fatal and nonfatal injuries occurring in 87,022 Massachusetts children and adolescents during a one-year period. A surveillance system for injuries at 23 hospitals captured 93 per cent of all discharges for ages 0-19 in the 14 communities under study. Sample data were collected on emergency room visits, hospital admissions, and deaths for all but a few causes of unintentional injuries. The overall incidence was 2,239 per 10,000. The true incidence rates are probably higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
2
11

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(106 citation statements)
references
References 12 publications
5
86
2
11
Order By: Relevance
“…Furthermore, because the majority of adolescent injuries treated in the ED are of minor severity and the adolescents are treated and released, the delivery of preventive inpatient services is not an option. 3 A recent study reported on the feasibility of using an interactive laptop program in the ED to prevent alcohol misuse among adolescents aged 14 to 18 years. 23 Use of such technology could overcome training, personnel, and time constraints that may be obstacles to delivering interventions in the ED.…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, because the majority of adolescent injuries treated in the ED are of minor severity and the adolescents are treated and released, the delivery of preventive inpatient services is not an option. 3 A recent study reported on the feasibility of using an interactive laptop program in the ED to prevent alcohol misuse among adolescents aged 14 to 18 years. 23 Use of such technology could overcome training, personnel, and time constraints that may be obstacles to delivering interventions in the ED.…”
Section: Importancementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Several studies have demonstrated the feasibility and effectiveness of delivering alcohol interventions to admitted adult trauma patients and to adults in the emergency department (ED). [15][16][17] Only 1 study has reported an effective ED-based intervention to decrease adolescent alcohol misuse and alcoholrelated problems among 18 and 19 year olds.…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…These were grouped under four broad headings: (1) maternal, (2) social/behavioral, (3) the home environment24 and maternal behavior25 were completed by trained ob¬ servers unaware of the objectives of the study.…”
Section: Determinant Factorsmentioning
confidence: 99%
“…5 Hospital discharge data and hospital emergency room records are increasingly being recognized as a valuable source of information for surveillance and research on non-fatal injuries. [6][7][8][9][10][11][12][13][14][15][16][17] Although they represent only a small proportion of all non-fatal injuries, hospitalized injuries are of particular concern since they are generally more severe and are associated with higher costs for medical care. 18 Emergency room and hospital discharge data on external causes of injuries have previously been reported from several industrialized countries.…”
mentioning
confidence: 99%